Sulfated, low-molecular-weight lignins are potent inhibitors of plasmin, in addition to thrombin and factor Xa: Novel opportunity for controlling complex pathologies - Henry, Brian L.; Aziz, May Abdel; Zhou, Qibing; Desai, Umesh R. (Thrombosis and Haemostasis, 2010)
Recently we prepared sulfated, low-molecular-weight lignins (LMWLs) to mimic the biological activities of heparin and heparan sulfate. Chemo-enzymatically prepared sulfated LMWLs represent a library of diverse non-sugar, aromatic molecules with structures radically different from the heparins, and have been found to potently inhibit thrombin and factor Xa. To assess their effect on the fibrinolytic system, we studied the interaction of LMWLs with human plasmin. Enzyme inhibition studies indicate that the three sulfated LMWLs studied inhibit plasmin with IC50 values in the range of 0.24 and 1.3 μM, which are marginally affected in the presence of antithrombin. Similarly, plasmin degradation of polymeric fibrin is also inhibited by sulfated LMWLs. Michaelis-Menten kinetic studies indicate that maximal velocity of hydrolysis of chromogenic substrates decreases nearly 70% in the presence of LMWLs, while the effect on Michaelis constant is dependent on the nature of the substrate. Competitive binding studies indicate that the sulfated LMWLs compete with full-length heparin. Comparison with thrombin-heparin crystal structure identifies an anionic region on plasmin as a plausible sulfated LMWL binding site. Overall, the chemoenzymatic origin coupled with coagulation and fibrinolysis inhibition properties of sulfated LMWLs present novel opportunities for designing new pharmaceutical agents that regulate complex pathologies in which both systems are known to play important roles such as disseminated intravascular coagulation.
Keywords: Plasmin; lignins; heparin mimetics; enzyme inhibition; allostery; anticoagulant; anti-fibrinolytic agent